(untitled) (Journal of Environmental Bioremediation and Toxicology, 2022)
One of the serious problems affecting the environment nowadays is petroleum hydrocarbon contaminations resulting from the activities in the oil and gas sector, these include: oil-spill, tank leakage, lubrication, petroleum exploitation, transportation, and services. Various techniques including mechanical and chemical methods have been employed for the bioremediation and degradation of hydrocarbons pollutants from the environments, however, some of these methods are generally expensive and may have detrimental effects on the environment, hence bioremediation is the alternative solution to hydrocarbon pollutants. Among microorganisms used in bioremediation technology nowadays, fungi are efficient, reliable, cost-effective, and environmentally friendly that can be used to cleanup and detoxify hydrocarbons contaminants from the environment viz; soil, water, and sediments. Bioremediation using fungi ensures the complete degradation and mineralization of petroleum hydrocarbon contaminants into carbon dioxide, water, inorganic compounds, and cell biomass. This review focuses on the potentials of fungi in the bioremediation of total petroleum hydrocarbons including the polycyclic aromatic hydrocarbons (PAHs). We reviewed and discussed current approaches in the bioremediation of hydrocarbon including the mechanisms of fungal bioremediation of hydrocarbon, which involves biosurfactants production and the use of fungal enzymes in the degradation of hydrocarbon pollutants. In general, fungi are more efficient and effective in the removal of hydrocarbon contaminants from the environments viz., water, soil, and sediments. However, the potentiality of fungi has not been exploited fully, hence further studies are recommended especially in the current genomic and proteomic era.